2006
DOI: 10.1051/0004-6361:20053745
|View full text |Cite
|
Sign up to set email alerts
|

An XMM-Newton survey of the Local Group galaxy M 33 – variability of the detected sources

Abstract: We present an analysis of the individual observations of a deep XMM-Newton survey of the Local Group spiral galaxy M 33. We detected a total of 350 sources with fluxes (in the 0.2-4.5 keV energy band) in the range 6.7 × 10 −16 −1.5 × 10 −11 erg s −1 . This comprehensive study considers flux variability, spectral characteristics, and classification of the detected objects. Thirty-nine objects in our catalogue are new sources, while 311 were already detected in a previous analysis of most of the same data using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 46 publications
3
55
0
Order By: Relevance
“…As noted earlier, this technique had been used by Ghavamian et al (2005) to confirm that two soft X-ray sources suggested as SNRs from XMMNewton surveys (Pietsch et al 2004;Misanovic et al 2006) are indeed SNRs based on their association with emission nebulae exhibiting high [S ii]:Hα ratios. We used the hardness ratio Vol.…”
Section: Soft X-ray Sources With Optical Counterpartsmentioning
confidence: 94%
See 1 more Smart Citation
“…As noted earlier, this technique had been used by Ghavamian et al (2005) to confirm that two soft X-ray sources suggested as SNRs from XMMNewton surveys (Pietsch et al 2004;Misanovic et al 2006) are indeed SNRs based on their association with emission nebulae exhibiting high [S ii]:Hα ratios. We used the hardness ratio Vol.…”
Section: Soft X-ray Sources With Optical Counterpartsmentioning
confidence: 94%
“…Later, using ROSAT, Long et al (1996) found X-ray counterparts to 10 optically identified SNRs. More recently, Misanovic et al (2006) reanalyzed the XMM-Newton data originally discussed by Pietsch et al (2004), identifying 15 non-variable X-ray sources with optical SNRs and suggesting 11 other X-ray sources might be SNRs based on their X-ray spectra. Ghavamian et al (2005) inspected interference-filter images of the candidates and found that two, XMM068 and XMM270, were located along lines of sight to nebulae with elevated [S ii]:Hα ratios that had been missed by Gordon et al (1998) as well as earlier optical observers.…”
Section: Introductionmentioning
confidence: 99%
“…If we assume that we have identified all foreground star candidates from the optical correlation and inspection of the optical images, the remaining sources can be classified as SNR candidates using the criteria given in Table 6. Similar criteria were used to select supernova remnant candidates in XMM-Newton observations of M 33 (Pietsch et al 2004;Misanovic et al 2006). Ghavamian et al (2005) and Long et al (2010) confirmed the supernova remnant nature of many of these candidates based on optical and radio follow-up observations.…”
Section: Supernova Remnantsmentioning
confidence: 99%
“…This pipeline was already used for the surveys of M31 (Pietsch et al 2005;Stiele et al 2011) and M33 (Pietsch et al 2004;Misanovic et al 2006). It was then enhanced for the analysis of the SMC survey by Richard Sturm (2012).…”
Section: Data Reductionmentioning
confidence: 99%